KEPATUHAN PELAPORAN TEMUAN MEDICATION ERROR OLEH TENAGA KEFARMASIAN PADA IMPLEMENTASI BUDAYA PATIENT SAFETY DI LIMA PUSKESMAS KOTA SEMARANG - Dewi, Adinta Citra; Suwarni, Sri; Indrasari, Ferika; Roslianti, Rini; Septiyana, Ria (LPPM Sekolah Tinggi Ilmu Farmasi Nusaputera, 2022)
Patient safety is a new discipline in health care that prioritizes the reporting, analysis, and prevention of medical errors that often lead to adverse events in health care. Prescription screening activities carried out by pharmaceutical personnel to prevent the occurrence of medication errors (Medication error) the purpose of the study was to determine the implementation of reporting the findings of medication error in prescription services on Patient Safety Culture reporting at five Primary Healthcare in Semarang City. This study is a non-experimental study, this study uses observational methods with quantitative data. Data collection with structured observation sheet instruments using the parameters of the Indonesian Minister of Health Regulation No. 11 of 2017 concerning Patient safety, the population of this study was the Patient Safety Team in five Primary Healthcare in Semarang city, namely 24 officers with total sampling technique. Analyze the results with a percentage range classification to determine the level of implementation. Compliance with reporting incident findings / medication errors as a form of implementation of patient safety culture in five Primary Healthcare in Semarang City has a high compliance value of 84.81% from the perspective of pharmaceutical personnel and is included in the high category.